Mezzanine momentum: A cross-continental examination of corporate financing trends - Ghosh Prosenjeet; Golder Uttam; Shanur Rahman Md.; Rumaly Nishat (Journal of Economics and Management)
Aim/purpose – Aside from conventional debt financing, mezzanine debt funding is an essential, nontraditional, and innovative instrument for financing a corporation. Nonetheless, the use and discussions on this particular type of financing are still limited. This study aims to investigate the nature and patterns of mezzanine debt financing and agreements at the global and regional levels, seeking to understand the trends and differences in its funding flows and deal movements across various continents so that businesses looking to grow abroad might use this analysis to identify places where mezza-nine finance is more accessible or advantageous. Moreover, investors can select the most appealing markets and conditions for mezzanine investments, thus improving their portfolios.